Comparison and prevalence of smoking among Saudi females from different Departments of the College of Applied Medical Sciences in Dammam - Ansari, Khalid; Farooqi, Faraz Ahmed (International Journal of Health Sciences, 2017)
Objectives: The aim of this study is to estimate the prevalence of smoking and factors associated with smoking habits among female students in all departments of College of Applied Medical Science (CAMS) at the University of Dammam. Methods: A cross-sectional study was conducted at CAMSs, University of Dammam. Only female students were included from all the departments of CAMS. The modified structured Global Youth Tobacco Survey was used to collect detailed information about smoking habits and factors associated with smoking. Results: A total of 332 out of 408 female students responded to the questionnaire with a response rate of 81%. The overall prevalence of those who tried smoking was 13.3%. Of those, 0.9% were active smokers. Among departments, Respiratory Care Department has the highest prevalence of smoking (25%; n = 11 out of 63) compared to clinical nutrition department where only 11.4% (n = 5 out of 54) either tried smoking or active smokers. The associated factors for smoking were high grade point average (P = 0.01). Interestingly, 61.3% of the sample reported that their first smoking trail was because of their experience to see someone they know is smoking (P = 0.01). Conclusion: The study results suggest that the prevalence of the current smoking is not significantly high. However, our data of this study suggests that some students tried to smoke in the past which may be considered as a risk factor of becoming regular smokers in the future. The study also reveals that the most common trigger to start smoking is their experience of seeing someone they know is smoking.